RouteBastion: Architecting a Broker for VRP APIs - Vieira, Pietro; Dalmazo, Bruno; Kreutz, Diego; Mansilha, Rodrigo Brandão (Anais da Escola Regional de Redes de Computadores (ERRC); 2024: Anais da XXI Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2024.4560, 2024)
The Vehicle Routing Problem (VRP) is a complex issue that requires advanced algorithmic problem-solving techniques and computational power. Major tech companies have developed cloud-based APIs to address this issue, offering solutions varying in cost, capabilities, and performance. However, selecting the right one for a given context is a challenging task, requiring balancing trade-offs, understanding long-term impacts, and adapting to future changes. RouteBastion, a Software as a Service (SaaS) platform, aims to unify and simplify the use of VRP-related APIs. Its modular, scalable architecture allows users to compare, select, and switch between APIs as their needs evolve. RouteBastion provides seamless integration, dynamic API selection, and decision-making, making it an intelligent middleware that enhances the flexibility and accessibility of vehicle route optimization. The paper will explore the system architecture and performance considerations to ensure RouteBastion can adapt to evolving industrial requirements.